FAKTOR-FAKTOR YANG MEMPENGARUHIKOMITMEN ORGANISASI - Wenny Winda Wulandari; Mukhammad Diki Candra; Rohmatus Sya’baniyah (Dar El-Falah, 2022)
Organizational commitment is a psychological bond between employees inan organization that is characterized by strong trust and acceptance oforganizational goals and values, a willingness to seek to achieveorganizational interests, and a strong desire to maintain their position asmembers of the organization. Aspects of organizational commitment: (a)affective commitment (b) normative commitment, (c) continuouscommitment. Ways that can be done to build organizational commitment:(a) Make it charismatic, (b) Build the tradition, (c) Provide extensive twoway communication, (d) Create a sense of community, (e) Build valuebased homogeneity , (f) Support employee development, (g) Commit toactualizing, (h) Provide first-year job collenge, (i) Provide developmentalactivities, (j) Commit to people-first values, (k) Hire "Right-kind" managers.Factors that influence employee commitment to the organization, namely:(a) Personal characteristics of workers, (b) Characteristics of work, (c)structural characteristics, and (d) Work experience.